The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Irrigation Water Pricing: The Gap Between Theory and Practice 2007
DOI: 10.1079/9781845932923.0021
|View full text |Cite
|
Sign up to set email alerts
|

Water pricing in irrigation: mapping the debate in the light of experience.

Abstract: This review provides a broad discussion of water pricing in agriculture. First, the practicalities and effectiveness of current water charging practices are described. Then, the main roles commonly attributed to irrigation water pricing are discussed: (1) cost recovery; (2) water conservation; (3) enhanced water productivity; (4) intersector reallocation; and (5) control of water quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 184 publications
0
37
0
3
Order By: Relevance
“…The cost recovery, efficiency and WDM can be achieved with lower unit price by volumetric based pricing methods. When such pricing method with carefully designed institutional structure is introduced, farmers adopt more efficient and water saving techniques [20]. The WTP estimation showed that volumetric pricing with well defined water rights and improved management of local water governance provide the best result from farmers' perspective.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost recovery, efficiency and WDM can be achieved with lower unit price by volumetric based pricing methods. When such pricing method with carefully designed institutional structure is introduced, farmers adopt more efficient and water saving techniques [20]. The WTP estimation showed that volumetric pricing with well defined water rights and improved management of local water governance provide the best result from farmers' perspective.…”
Section: Final Remarksmentioning
confidence: 99%
“…The transaction cost depends on water governance as well as water rights and other water institutions. In the current water scarce situation, volumetric pricing is expected to give the best incentive for farmers to increase water use efficiency (Molle and Berkoff [20]). The cost recovery, efficiency and WDM can be achieved with lower unit price by volumetric based pricing methods.…”
Section: Final Remarksmentioning
confidence: 99%
“…"Indirect fees" and "revenue-only" fees are found in some of the smaller canal companies that deliver water to their members on a per-hectare or per-time unit basis. Molle and Berkoff (2008) describe several goals of irrigation pricing, within the context of policy tools. In particular, water pricing can serve as a financial policy tool by ensuring that some portion of the costs of constructing and operating an irrigation project are recovered.…”
Section: Cost Componentsmentioning
confidence: 99%
“…State and federal water agencies and the irrigation districts with which they enter contractual relationships often establish prices that include one or more components reflecting policy goals that align somewhat with the Molle and Berkoff (2008) policy tools. For example, irrigation water prices in the federal Central Valley Project in California include cost recovery charges (financial policy goal) and an environmental restoration charge (environmental policy goal).…”
Section: Cost Componentsmentioning
confidence: 99%
“…This condition calls for the imposition of flat rates by the water provider, even if the level of use varies. With flat rates, users are taken to have similar access and are charged equally across farms and land [21], i.e., the tariff is the same per hectare of land for all farms. Indeed, the regions supplied by surface irrigation network are usually very large and comprise huge extensive farms irrigating only a small quota of the cultivated agricultural land or specialized small fruit and vegetable farms irrigating most of the cultivated land.…”
Section: Background Literaturementioning
confidence: 99%